Potensi Penyerapan Tenaga Kerja di Koperasi Jawa Barat Tahun 2020 Menggunakan Structural Equation Model - Agrivinie Rainy Firohmatillah; Adri Arisena (Program Studi Magister Manajemen, Institut Manajemen Koperasi Indonesia, 2021)
Labor absorption in the cooperative sector in West Java is still relatively low at 10,434 people or 0.05 percent. Based on this fact, the absorption of labor in the cooperative sector can still be increased in line with the program of the Ministry of Cooperatives and MSMEs in implementing total cooperative reform through three strategic measures, namely Reorientation, Rehabilitation and Development. Therefore, it is expected that the absorption of labor in the cooperative sector of West Java is increasing. To find out and see this, this research was done. The categories of respondents in this study are divided into two groups, namely the group of member respondents and the non-member respondent group. The analysis used to see the potential used descriptive analysis, while the Structural Equation Model (SEM) was used to see how much work stress, job satisfaction affect turnover intention for non-member groups of respondents. For the respondent group SEM members were used to see how much work stress, job satisfaction, and turnover intention affect member participation and cooperative development. The results showed that for the non-member respondent group both variables had a significant influence on turnover intention, while for the group of respondents members pointed out that the three variables had a significant direct influence on member participation and cooperative development.